Constitutionality of the probatory initiative of the judge in the presentation of evidence in the civil process - Obando Blanco, Víctor Roberto (2008)
Being the end of the process a public interest of the State, the judge has probatory initiative for the search of the judicial conviction, however this initiative is limited to the elucidation of the facts that the parties have not proof in a suitable way. The Civil Procedural Code omits in the design of the application of the proofs ordered by the judge the limits on the probatory initiative, omission that must be corrected through a systematic interpretation of the articles 188 and 190 of the Code as a result of the legal interpretation, and going to the procedural doctrine that has established as limits: a) That the judge's test is limited to the following controversial facts; b) The source of the proof must appear in the process; and c) Regarding the principle of contradiction and the right of defense of the parties, allowing to extend its initially proposed tests.